Benefits of solar forecasting for energy imbalance markets. (February 2016) - Kaur, Amanpreet; Nonnenmacher, Lukas; Pedro, Hugo T.C.; Coimbra, Carlos F.M.
Abstract: Short term electricity trading to balance generation and demand provides an economic opportunity to integrate larger shares of variable renewable energy sources in the power grid. Recently, many regulatory market environments are reorganized to allow short term electricity trading. This study seeks to quantify the benefits of solar forecasting for energy imbalance markets (EIM). State-of-the-art solar forecasts, covering forecast horizons ranging from 24 h to 5 min are proposed and compared against the currently used benchmark models, persistence (P) and smart persistence (SP). The implemented reforecast of numerical weather prediction time series achieves a skill of 14.5% over the smart persistence model. Using the proposed forecasts for a forecast horizon of up to 75 min for a single 1 MW power plant reduces required flexibility reserves by 21% and 16.14%, depending on the allowed trading intervals (5 and 15 min). The probability of an imbalance, caused through wrong market bids from PV solar plants, can be reduced by 19.65% and 15.12% (for 5 and 15 min trading intervals). All EIM stakeholders benefit from accurate forecasting. Previous estimates on the benefits of EIMs, based on persistence model are conservative. It is shown that the design variables regulating the market time lines, the bidding and the binding schedules, drive the benefits of forecasting. Highlights: Benefits of solar forecasting for Energy Imbalance Markets are presented. Reforecast model for day-ahead solar prediction achieves a skill of 14.5%. Flexibility reserve requirement reduces by 21% for 5-min trading intervals. Probability of an imbalance can be reduced by 19.65% using solar forecasts. Design variables regulating the power grid drive the benefits of forecasting.